2003
DOI: 10.1159/000074243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxytocin Outside Pregnancy

Abstract: For a long time, oxytocin was regarded as a pregnancy hormone released by the hypophysis to stimulate labour and milk ejection. In the present survey, data have been collected from the literature to show the spectrum of the hitherto known functions of oxytocin outside pregnancy. It is now known that oxytocin receptors can occur almost ubiquitously in the organism, that oxytocin is also formed outside of the brain and that oxytocin has functions in a number of organs. In the first part of the survey, stimuli th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 66 publications
(74 reference statements)
0
26
0
Order By: Relevance
“…Studies have shown that OT is released into the circulation as a direct response to CS. This has been demonstrated in sheep (26), rats (36), and humans (the Ferguson reflex) (14,27,30). The main goal of this study is to determine whether a sustained PRL rhythm can be triggered by a single injection of OT.…”
mentioning
confidence: 92%
“…Studies have shown that OT is released into the circulation as a direct response to CS. This has been demonstrated in sheep (26), rats (36), and humans (the Ferguson reflex) (14,27,30). The main goal of this study is to determine whether a sustained PRL rhythm can be triggered by a single injection of OT.…”
mentioning
confidence: 92%
“…This response promotes affiliative and social behaviour in response to stressful circumstances (Boutet et al, 2006;Engelmann et al, 2004;Lippert et al, 2003), maximising fitness through care (or 'tending') of offspring or others during periods of stress. However, the relationship in which OT suppresses or attenuates stress response is neither straightforward nor universal.…”
Section: Oxytocin and Stressmentioning
confidence: 99%
“…Within the periphery the OTR is localized in a number of different organs including the uterus and mammary glands. In the uterus it is involved in the onset and progression of labor and OT has been long regarded as a pregnancy hormone 20 as it stimulates labor and milk ejection.…”
Section: Structure and Function Of Ot And The Otrmentioning
confidence: 99%